Postgraduate specialties interest, career choices and qualifications earned by male dentists graduated from King Saud University - Yousef H. Al-Dlaigan; Ra'ed Al-Sadhan; Mohammed Al-Ghamdi; Abdullah Al-Shahrani; Mohammed Al-Shahrani (Elsevier, 2011)
Objectives: To study the career development of male graduates of King Saud University (KSU), College of Dentistry in terms of pursuit of postgraduate dental education, higher degrees or Board Certification, choice of universities and countries of study, and place of work after qualification.Methods: A questionnaire survey was carried out through face to face or telephone interview among 666 KSU graduates of 1982-2004.Results: 80% (532 graduates) response rate. (77%) finished postgraduate dental education. 17% specialized in Prosthodontics, 16% in Saudi Board Advanced Restorative Dentistry, 14% in Advanced General Dentistry, 10.5% in Orthodontics, 10% in Oral and Maxillofacial Surgery, 8.3% in Pediatric Dentistry, 7.7% in Endodontics, 6% in Periodontics, 5.5% in Operative Dentistry, 5% in other Specialties. 61% had a Master's degree and 16% had a Doctorate degree. 23% had Board Certificates and 8% had a Fellowship Certificate. (78%) are working in the government, 15% at the university and 6% in private, and 19% in administrative positions.Conclusion: Most of the dental graduates were motivated and eager to continue their postgraduate education to get either clinical specialty or academic degrees from nationally and internationally well recognized and known Universities and programs. Keywords: Graduate, Dental, Specialty, Career, Education, Postgraduate